2020
DOI: 10.1111/ssqu.12860
|View full text |Cite
|
Sign up to set email alerts
|

Gun Ownership and Life Satisfaction in the United States

Abstract: ObjectiveAlthough there is little empirical evidence linking gun ownership with personal well‐being, speculation is widespread in gun culture. In this article, we test whether people who own guns are more or less satisfied with their lives than people who do not own guns.MethodsWe employ data collected from three national surveys, the Baylor Religion Survey (2014), the Chapman University Survey on American Fears (2014), and the General Social Survey (2018) to formally assess this understudied association.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Pandemic gun purchases and gun-related violence have been at least partially motivated by widespread uncertainty and fear, trauma and loss ( Caputi et al, 2020 , Kravitz-Wirtz et al, 2021 , Lyons et al, 2021 ). One reason for these motivations is the idea that guns may somehow empower their owners by contributing to a subjective sense of personal control over life ( Hill et al, 2020 , Mencken and Froese, 2019 ). These themes clearly dovetail with our profile of recent gun purchasers.…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic gun purchases and gun-related violence have been at least partially motivated by widespread uncertainty and fear, trauma and loss ( Caputi et al, 2020 , Kravitz-Wirtz et al, 2021 , Lyons et al, 2021 ). One reason for these motivations is the idea that guns may somehow empower their owners by contributing to a subjective sense of personal control over life ( Hill et al, 2020 , Mencken and Froese, 2019 ). These themes clearly dovetail with our profile of recent gun purchasers.…”
Section: Discussionmentioning
confidence: 99%
“…Gun owners make a lot of claims about guns. Many will tell you that guns improve their lives, make them happy, and help them to sleep better at night, but none of these claims have been established empirically (Hill, Dowd-Arrow, Davis, et al, 2020; Hill, Dowd-Arrow, Burdette, Hale, et al, 2020; Hill, Dowd-Arrow, Burdette, Warner, et al 2020). People who do not own guns will tell you that gun owners are motivated by impotence and fear, but these ideas are also unfounded (DeFronzo, 1979; Dowd-Arrow et al, 2019; Hauser & Kleck, 2013; Kleck, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…2019; Hill et al. 2020a, 2020b, 2022). Studies of religiosity and gun‐related outcomes have been identified as especially “rudimentary” (Ellison et al.…”
mentioning
confidence: 98%
“…As Yamane (2017) has noted, sociological perspectives on guns have been surprisingly underdeveloped. Although recent special issues on "guns and society" have attempted to broaden this area of study (Dowd-Arrow, Hill, and Burdette 2020;Steidley and Yamane 2022), scholars have mostly focused on a narrow range of research topics, including patterns and correlates of gun ownership (Dowd-Arrow, Hill, and Burdette 2019;Legault 2008), the changing cultural meanings associated with owning and using firearms in the United States (Carlson 2015b;Mencken and Froese 2019), and the relationship between gun ownership and well-being (Dowd-Arrow et al 2019;Hill et al 2020aHill et al , 2020bHill et al , 2022. Studies of religiosity and gun-related outcomes have been identified as especially "rudimentary" (Ellison et al 2021).…”
mentioning
confidence: 99%